Regional inequality of economic outcomes and opportunities in Ethiopia: A tale of two periods - Bethlehem A. Argaw (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2017)
This paper provides an informative picture of the extent of regional inequality of economic outcomes and opportunities in the pre-and post-reform Ethiopia. We start by presenting evidence that regional inequality in educational attainment, formal employment, and access to safe water and sanitation facilities declined substantially between the mid-1990s and late 2000s. When we measure regional inequality of opportunities using the intergenerational persistence of educational attainment, we find a moderate increase in intergenerational mobility at the national level and a declining gap across regions. Given the regional concentration of ethnic and language groups in Ethiopia, further reducing the unequal distribution of economic outcomes and opportunities across regions have important implications for the political stability and economic development of the country.
Keywords: D39; D18; I24; I28; 330; horizontal inequality; intergenerational mobility; economic outcomes; Ethiopia